The Impact of Incentives on the Performance Level of Nursing Staff in the Libyan Public Health Sector - Abdelsalam M. A. Saad (Scientific Journal of University of Benghazi, 2020)
Several studies have dealt with the issue of incentives and its impact on job satisfaction and the level of performance, and urged in their recommendations the need to study incentives to raise the level of performance in institutions. Hence, this study sought to identify the incentive system followed in the public health sector in Libya, and its impact on the performance of the nursing staff. The Statistical Package for Social Sciences (SPSS) was used to analyse the data collected through a questionnaire of 643 male and female nurses. The results showed that the level of financial and moral incentives provided to nursing staff in the public health sector in Libya is insufficient and inappropriate and that it uses negative incentives by applying disciplinary measures, more than using positive incentives. The results also showed that the sample members are satisfied in general with the level of their work performance. And that there is an of incentives on the performance level. Thus, the incentive system followed in the public health sector in Libya, to some extent, impacts the level of performance.